A critical discourse analysis on the presentation of Filipino values in Pinoy Dream Academy Season Two - Panao, Florence De La Cruz (2009.)
"The primary focus of this research was to know the ways Filipino values were presented in Pinoy Dream Academy Season II. Using the framework of Jocano, this study sought to answer how halaga, asal and diwa--the ones that make up the Filipino Value System, were presented in the program. This study used the approach of the Critical Discourse Analysis and the concept of Representation in the analysis. Taking all thirteen (13) episodes of the PDA Season Two spanning from July to August 2008, the results of this study showed that traditional and new forms and expressions of Filipino values were present in the program. There have been resistances and alterations in terms of definition and degree of expression which paved way to a new form of Filipino values. With this result, the researcher concluded that the identity of the Filipinos is being negotiated through the constant pull and push of traditional and new forms of Filipino values. Philippine society can be said to belong to a still pre-modern society but attempts have already been made to make it industrial such that resistances and negotiations to traditional forms of Filipino values were found present in program. The program was a rich battlefield of this negatiation of the Filipino identity."
Thesis (M.A. Media Studies (Broadcasting)--University of the Philippines, Diliman.
Vita.
Keywords: Reality television programs -- Philippines; Values -- Philippines; Discourse analysis